Treatment of patients with brain metastases from ovarian cancer: clinical observation - V. B. Karakhan; D. R. Naskhletashvili; N. V. Sevyan (ABV-press, 2014)
The capacity of drugs to penetrate across the blood-brain barrier (BBB) is primarily traditionally taken into account on choosing chemotherapy (CT) regimens for patients with brain metastatic involvement. P aclitaxel and carboplatin have a low ability to cross the BBB in its normal state. As of now, there is experimental and clinical evidence for BBB dysfunction in brain metastases. The described case serves as another evidence for the successful application of standard approaches to choosing CT regimens for patients with platinum-susceptible recurrent ovarian cancer when the disease recurs and progresses as brain metastatic involvement. The authors also show the effe ctive use of combination treatment: CT in combination with radiation treatments (stereotactic radiosurgery and conventional whole brain radiotherapy) with complete tumor regression being achieved in a patient with ovarian cancer and brain metastatic involvement.